(untitled) (World Bulletin of Social Sciences, 2025)
In linguopolitology, which is recognized as a new branch of linguistics, discourse, particularly political discourse, holds a special place. The theory of discourse in communication began to take shape as an independent field of study in the mid-1960s. During this period, scholars’ tendency to view language as an inseparable means of communication found its expression in the study of texts. As linguistics gradually moved beyond its structural and formal-functional framework, shifting toward a comprehensive, holistic, and consistent study of language, the term discourse started to be actively used. In this process, examining its relationship with the concept of “text” became an important area of research. The social nature of discourse has led to the emergence of new concepts such as innovative discourse, journalistic discourse, political discourse, scientific discourse, literary discourse, and evaluative discourse. This, in turn, underscores the relevance of studying discourse from a theoretical perspective. The following analysis focuses on interpretations of discourse and political speech theory within global linguistics.